Insights to microsporidia Nosema bombycis congenital infection and host immune responses in the embryo and larva stages of silkworms - Tangxin Li; Yue Song; Quan Sun; Qiong Yang; Yunlin Tang; Zigang Shen; Zhangshuai He; Yabin Dou; Junzheng Zhang; Sheng Li; Tian Li; Xianzhi Meng; et al. (BMC Genomics)
Abstract Microsporidia are a group of intracellular and unicellular eukaryotic parasites, which can nearly infect all animals, including human beings. As the first identified microsporidia, Nosema bombycis is a world-wide threat for silkworm eggs production, it can cause the congenital infection via transovarial transmission. It is important for pathogenesis elucidation to unravel the molecular characteristics of N. bombycis proliferation and host immune responses to the congenital infection in embryo and larva stage. Here, we adopted dual RNA-seq approach to investigate and compare the dynamic molecular pattern of pathogen proliferation and host immune responses between diapause and non-diapause silkworm eggs. Our results showed the N. bombycis proliferation in non-diapause silkworm eggs is a continuous process, many parasites enter the sporogony stage at 2 days post-oviposition (dpo). For newly hatched larva (1 dph), the abundance of pathogen mRNA sequences is up to 2.32% in non-diapause strain, far higher than 0.34% of diapause strain, the main reason is the hot HCl bath treatment at 24 h post-oviposition for diapause silkworm eggs with the aim to free the egg diapause. As to immune responses, whatever for diapause strain or non-diapause strain, there is stronger immune responses to congenital infection in larva stage than that of embryo stage, however, the host immune responses to congenital infection are fairly different between non-diapause and diapause strains of silkworms, especially in embryo stage. We found the surprising “First day Chaos” that there are 6,071 differential expressed genes (DEGs) at 1 dpo for non-diapause strain between infection group and uninfected group, but decreases dramatically to 109 DEGs at 2 dpo. In non-diapause strain, the earliest DEGs of antimicrobial peptides were up-regulated at 1 dpo, then is 5 dpo with up-regulated lebocin, 7 dpo with morLP-B1, morLP-B4. For non-diapause strain, the well-established immune responses were observed in newly hatched larvae. On the contrast, for diapause strain, the earliest DEGs of AMPs appear at 5 dph, the mature immune responses are well established at 5 dph too. In non-diapause silkworms, we observed obvious pathogen’s regulation in the main immune pathways including Toll, IMD, JAK-STAT and melanization at the different steps such as immune recognition, signal modulation and transduction, effectors. Taken together, our results for the first time provide a global molecular view of microsporidia proliferation and innate immunity responses in a congenital infection system and provide some new insights into immune development and establishment in the embryo and early larva stage of Bombyx mori.